Answer:
4. Slope of function B = -slope of function A
Explanation:
Given:
Function A is given as:
![F(x)=-2x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yn029e3xf7e8cmjrkxe0egrshfhmr5jp95.png)
The above equation is of the form
, where
represents slope of the line.
Therefore, on comparing the function A with the above standard form, er conclude that, slope of function A is -2.
Now, from the graph of function, we consider any two points on the graph and determine the slope of the line using the two points.
Let us consider the points
![(x_1,y_1)=(1.5,0)\ and\ (x_2,y_2)=(3,3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ngm5loqkcc4p8hy8jfhkguskguyry9v7v0.png)
Now, the slope of the line passing through these two points is given as:
![m_B=(y_2-y_1)/(x_2-x_1)=(3-0)/(3-1.5)=(3)/(1.5)=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2q3sobjhqbuir9yvlngbchxl8k24xtfqcg.png)
Therefore, slope of function B is 2.
Therefore, the correct relation between the slopes of the two functions is that the slope of function B is negative of the slope of function A.
![m_B=-(m_A)=-(-2)=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f9sce5j66csvo4h94i4nszgvthwj0a5j9l.png)